Pengaruh Kualitas Produk, Persepsi Harga, Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Al-Buraq Cafe - nabila salsabillah; Rully Arifiansyah (LPPM Universitas Asa Indonesia, 2022)
The purpose of this study was to determine how different factors (product quality, price perception, and service quality) affect purchasing decisions. The subjects of this research are customers or visitors of Al Buraq cafe. Sampling method using accidental sampling method selected as many as 120 respondents. The data collection method used a questionnaire distributed to respondents, and this analysis used multiple regression. The results show that product quality has an effect of 34% on purchasing decisions, price perception variables have an influence of 29% on purchasing decisions, service quality variables affect purchasing decisions by 35%. The results of the analysis concluded that product quality, price perception, and service quality partially or simultaneously influence purchasing decisions at Al Buraq cafe. The independent variables which include product quality, price perception and service quality accounted for 22% of purchasing decisions. And the remaining 88% are other variables that are not included in the scope of this study.